2019
DOI: 10.1016/j.afjem.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Trauma intensive care in a terror-ravaged, resource-constrained setting: Are we prepared for the emerging challenge?

Abstract: Introduction Trauma in developing countries has been on the increase, a situation perpetuated by rising road traffic collisions, terrorism and firearms proliferation. Some of the victims of trauma are left with life threatening conditions requiring urgent surgical intervention and/or intensive care. The objectives of this study were to determine the pattern of major trauma needing intensive care in the region, and to determine the outcome of major trauma admitted to intensive care unit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Together, they serve as indicators of a population's health status with respect to a portfolio of health conditions and diseases. It is estimated that approximately 5-20 percent of combat-related casualties during the first ten years of OIF and OEF involved severe burns (Breederveld and Tuinebreijer, 2009;Wolf et al, 2006); this is consistent with a variety of estimates from other recent conflict settings, such as Mali (Akpoto et al, 2015), Nigeria (Amaefule et al, 2019;Dabkana et al, 2015), and Israel and Palestine (Mosleh et al, 2018).…”
Section: Incidence and Prevalence Of Burn Injuriessupporting
confidence: 74%
“…Together, they serve as indicators of a population's health status with respect to a portfolio of health conditions and diseases. It is estimated that approximately 5-20 percent of combat-related casualties during the first ten years of OIF and OEF involved severe burns (Breederveld and Tuinebreijer, 2009;Wolf et al, 2006); this is consistent with a variety of estimates from other recent conflict settings, such as Mali (Akpoto et al, 2015), Nigeria (Amaefule et al, 2019;Dabkana et al, 2015), and Israel and Palestine (Mosleh et al, 2018).…”
Section: Incidence and Prevalence Of Burn Injuriessupporting
confidence: 74%
“…Traumatic brain injuries are by far the leading cause of trauma related deaths in our ER (82.5%). Amaefule et al [27] also showed that traumatic brain injuries caused more deaths (66.2%) within the first 72hours in the ER than all other causes combined. Etebu and Ekere [28] in a similar study 2 decades ago in the same institution showed that traumatic brain injury was the leading cause of trauma-related deaths in children.…”
Section: Distribution Of Mechanisms Of Mortalitymentioning
confidence: 96%
“…30 For example, a retrospective cohort study of trauma patients in a Northwestern Nigerian hospital demonstrated that the said cases exceeded the capacity of their respective intensive care units. 30 Furthermore, policies installed by active terrorist groups, such as the Taliban's ban on female patients seeking medical care at hospitals in Kabul, mediate difficulties in accessing the necessary healthcare services. 22 These barriers to healthcare are worrisome as they result in poorer chronic disease management, an increase in the burden of avoidable illness and comorbidities, and early mortality.…”
Section: Disrupting Healthcare Access and Services For Citizensmentioning
confidence: 99%